Debt versus Equity in Corporate Financing: Distinction and Resemblance Between Agency Theory and Market Timing Theory in Capital Structure Decisions - Hamad, Samer (European Scientific Journal, ESJ, 2025)
This study examines the preference for debt over equity issuance among U.S. companies and analyzes the financial and structural implications of financing decisions by focusing on the interplay between agency theory and market timing theory. The research investigates how these theories explain financing preferences, assesses the impact of key financial ratios on debt levels, and explores the implications for corporate financial strategies. The research employed a quantitative panel data regression analysis, utilized secondary data from 64 U.S. companies over quarterly periods between 2012 and 2017, and sourced from the Securities and Exchange Commission (SEC). Analytical techniques include the Mahalanobis Distance for outlier detection, Pearson’s correlation matrix for multicollinearity assessment, and Hausman and Lagrange multiplier tests were used to validate the fixed-effects model. Findings reveal that companies tend to issue debt to reduce their tax liabilities and increase post-tax cash flow available for dividends. However, a negative relationship is observed between liquidity, measured by the current ratio (CR), and the debt ratio, suggesting that higher liquidity levels lead companies to limited debt, potentially to mitigate agency costs between creditors, management, and owners. Additionally, the negative relationship between company size and debt ratio indicates that larger companies, with higher profitability, tend to maintain lower debt levels. Conversely, asset utilization shows a positive relationship with debt, indicating efficient asset use supports higher borrowing capacity. Notably, share price performance and tangibility were statistically insignificant, implying that market timing has limited influence on debt decisions. The findings highlight the complex dynamics of capital structure decisions, which emphasize the importance of aligning management incentives to maximize shareholders’ value while minimizing agency costs. This alignment process would be achieved through performance-based compensation, which is tied to liquidity optimization, profitability, growth opportunities and stock price performance. The study provides a comprehensive evaluation of how equity and debt financing preferences impact corporate financial strategies and behaviors. The study highlights the benefits from tax advantages of debt financing, which enhances post-tax cash flow. The research contributes to the broader understanding of corporate financing strategies in developed markets, though further studies could explore cross-market comparisons.